Implementasi RFID untuk Mengatasi Untraceable Book Pada Perpustakaan - Ahmad Fajri Rahman; Agung Setia Budi; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The library is a place to store and read collections of reading material such as books. Each book has its own identity which is stored in the catalog. In this technological era, the type of catalog used is OPAC (Online Public Access Catalog). Generally, markers of identity numbers on books are barcodes. The process of writing a catalog (cataloging) is usually done only once (semi-permanent). Library visitors can access the catalog to find the book you want, but sometimes when searching for books there is a problem that the book is not found on the shelves listed in the catalog. Based on this, the system was created with the aim of automatically updating catalogs. This system cannot be implemented on a barcode system, because in general barcode reader devices read data through a USB port, so if you want to access the database you must use a mini computer. Another alternative that can be used to solve this problem is RFID (Radio Frequency Identification) technology. The implementation of the RFID system is done by replacing the barcode system with RFID which is implemented on the nodemcu in order to access the database and can do the catalog update process when there are books scanned on the RFID scanner. The system test results show that the system can detect and read RFID tags at a certain radius and do a catalog update with a duration of less than 5 seconds.